Delphinidin-3-O-glucoside inhibits angiogenesis via VEGFR2 downregulation and migration through actin disruption - Viegas, Olga (2019)
Excessive angiogenesis favours cancer development, allowing cancer invasion. Polyphenols are promising chemopreventive agents, although data gather so far in respect of anthocyanins, namely cyanidin-3-O-glucoside and delphinidin-3-O-glucoside (DG) and respective aglycones are scarce. The capability of these compounds to prevent tumour progression by inhibiting angiogenesis/cell migration/proliferation was studied in: (i) chicken embryo chorioallantoic membrane assay; (ii) MDA-MB-231/MCF-12A cells to study proliferation and vascular endothelial growth factor receptor-2 (VEGFR-2) expression and cytoskeleton dynamics; (iii) in vitro assay to evaluate gastrointestinal digestion. The studied compounds promoted alterations on actin re/disassembly to form protrusions/stress fibres, evidencing capability to disrupt actin cytoskeleton dynamics and inhibiting angiogenesis, at least in part, by VEGFR-2 downregulation, with DG presenting the higher effect. Anthocyanin evidenced selectivity towards cancer cells by eliciting cytotoxicity on MDA-MB-231 cells and having a slight effect on healthy cells. Thus, DG evidenced the most promising profile as dietary supplement to achieve the biological desired effects.